2009
DOI: 10.1038/sj.bjc.6604845
|View full text |Cite
|
Sign up to set email alerts
|

Promoter CpG methylation in cancer cells contributes to the regulation of MUC4

Abstract: Mucin 4 (MUC4) is a high molecular weight transmembrane mucin that is overexpressed in many carcinomas and is a risk factor associated with a poor prognosis. In this study, we show that the DNA methylation pattern is intimately correlated with MUC4 expression in breast, lung, pancreas and colon cancer cell lines. We mapped the DNA methylation status of 94 CpG sites from À3622 to þ 29 using MassARRAY analysis that utilises base-specific cleavage of nucleic acids. MUC4-negative cancer cell lines and those with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 24 publications
6
61
3
Order By: Relevance
“…The target region of MSP locates CpG sites 108-112 of MUC4 promoter, which may play an important role in MUC4 expression [23]. Primer sets for amplification of the MUC4 unmethylated and methylated sequences were synthesized as the reference sequence [23]. PCR was performed using a TaKaRa Taq PCR kit (TaKaRa, Otsu, Shiga, Japan).…”
Section: Dna Extraction From Microdissectates Bisulfite Treatment Anmentioning
confidence: 99%
See 3 more Smart Citations
“…The target region of MSP locates CpG sites 108-112 of MUC4 promoter, which may play an important role in MUC4 expression [23]. Primer sets for amplification of the MUC4 unmethylated and methylated sequences were synthesized as the reference sequence [23]. PCR was performed using a TaKaRa Taq PCR kit (TaKaRa, Otsu, Shiga, Japan).…”
Section: Dna Extraction From Microdissectates Bisulfite Treatment Anmentioning
confidence: 99%
“…Two microgram of DNA per sample was bisulfite converted and cleaned up using an Epitect Bisulfite Kit (Qiagen). The target region of MSP locates CpG sites 108-112 of MUC4 promoter, which may play an important role in MUC4 expression [23]. Primer sets for amplification of the MUC4 unmethylated and methylated sequences were synthesized as the reference sequence [23].…”
Section: Dna Extraction From Microdissectates Bisulfite Treatment Anmentioning
confidence: 99%
See 2 more Smart Citations
“…This was also reported that Methylation of CpG near the transcriptional start site was inversely correlated with MUC1 gene expression (Yamada et al, 2008). Similarly, MUC4 expression was also regulated by methylation of CpG sites near the transcriptional start site (N Yamada et al, 2009).…”
Section: 10299 Epigenetic Changes Within Promoter Regions Of Antigenmentioning
confidence: 60%